(De)constructing our migrant neighbours: regional and international impacts of the Venezuelan crisis in the Caribbean. (4th May 2021) - Wallace, Wendell C.; Mortley, Natasha K.
ABSTRACT: This introductory chapter presents a background to the Venezuelan migrant crisis impacting the Caribbean region. While migration is deeply embedded in Caribbean history and culture, the movement of Venezuelans into the region, characterized mainly by displaced migrants, presents new dynamics never experienced before. This chapter describes the emerging Venezuelan situation as a 'crisis' in light of Caribbean communities unpreparedness in terms of protocols, policy and capacity for dealing with the influx of displaced migrants. Within this context, the Editors thus make a case for the need for reconceptualization, empirical research and new frameworks for action among Caribbean migration scholars. The chapter ends with a summary of the seven articles contained in this special issue, demonstrating their multi- and interdisciplinary focus, as well as the various methodological tools employed by the authors in bringing indigenous, rights-based, gender sensitive perspectives to the Venezuelans displacement and its impact for the Caribbean region.